2018
DOI: 10.3389/fped.2018.00137
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Children's Health Behaviors, Attitudes, and Body Mass Index After a 10-Week Lifestyle Intervention With Follow-Up

Abstract: Background: Given the current global child obesity epidemic, testing the effectiveness of interventions in reducing obesity and its influencers is paramount. The purpose of this study was to determine immediate and long-term changes in body mass index and psychosocial variables following a 10-week lifestyle intervention.Methods: Seven hundred and seventy participants (8.75 ± 0.98 years of age, 379 boys and 391 girls) took part in the study. Participants had height, weight, and psychosocial questionnaires asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…In the current paper, ordinary BMI and waist circumference have been observed in both models. Similar results were observed by Brown et al (2018), obtaining that BMI improved when the intervention is oriented to lifestyle habits. Since Nuttall (2015) observed that BMI has some limitations due to it does not differentiate between fat mass and lean mass, Elia (2013) has recommended the use of bioelectrical impedance devices to identify the kind of body mass.…”
Section: Discussionsupporting
confidence: 85%
“…In the current paper, ordinary BMI and waist circumference have been observed in both models. Similar results were observed by Brown et al (2018), obtaining that BMI improved when the intervention is oriented to lifestyle habits. Since Nuttall (2015) observed that BMI has some limitations due to it does not differentiate between fat mass and lean mass, Elia (2013) has recommended the use of bioelectrical impedance devices to identify the kind of body mass.…”
Section: Discussionsupporting
confidence: 85%
“…This review included 19 intervention studies that reported a significant increase in children’s consumption of a healthy diet, mainly consisting of fruit and vegetables. Overall, 6 studies of these articles included only educational components [ 35 , 36 , 40 , 41 , 47 , 51 ], 6 studies used practical approaches [ 37 , 38 , 42 , 44 , 48 , 50 ], and 7 included both approaches [ 34 , 39 , 43 , 45 , 46 , 49 , 52 ]. The intervention programs and their duration can be seen in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, participation in these programs increased self-confidence in cooking, enjoyment of food and cooking, frequency of cooking at home, availability of fruits and vegetables at home, use of nutrition labels when shopping, and knowledge of bedtime routines [ 34 , 35 ]. Moreover, food waste [ 45 ], total fat intake [ 34 ], and the percentage of daily calories from morning and afternoon snacks [ 52 ], such as cookies, cakes, chocolates [ 37 , 48 ], and sugary drinks [ 34 ], were reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, schools play significant roles to improve children's understanding towards clean and healthy living behaviors (CHLB). 17 These CHIBs in school-aged children are essential, since they are prone to health problems, including infectious diseases. 18 The high frequency of social interaction, along with age-related behavioral, and environmental factors, can promote the spread of infectious diseases within Islamic Boarding Schools, which can then spread to homes and the larger community.…”
Section: Discussionmentioning
confidence: 99%